Association between hypertension and quality of life in pregnancy. (2nd July 2016) - Patrícia Medeiros Falcão, Kellly; Pedrozo Campos Antunes, Thaiany; do Nascimento Andrade Feitosa, Ankilma; Victor, Edgar Guimarães; Nunes Alves de Sousa, Milena; de Abreu, Luiz Carlos; Vilar de Asis, Elisangela; Barros de Quental, Ocilma; Pinheiro Bezerra, Italla Maria; Azevedo de Freitas Junior, Humberto
ABSTRACT: Purpose : To assess the association between hypertension in pregnancy and women's quality of life (QoL) and the variation in the quality of life over gestational trimesters. Method : A questionnaire was applied to 194 hypertensive pregnant women and 195 pregnant women without complications. The questionnaire was composed of two parts: socioeconomic profile and specifically QoL, using the instrument Ferrans & Powers Quality of Life Index. All women included underwent a physical examination. Results : Blood pressure was found to be approximately 20 mmHg higher in hypertensive pregnant women compared to pregnant women without complications. All QoL domains of hypertensive pregnant women had lower scores than those of pregnant women without complications, with health/functioning rated the lowest, averaging 17.63. The least affected domain was family, having the best average score (26.0). The QoL had no significant variations in relation to gestational trimesters. Conclusions : Pregnancy causes intense changes, both physical and psychological, in women's lives and hypertension was found to be a factor of high interference in pregnant woman's QoL, causing lower scores in all QoL domains of hypertensive pregnant women, compared with pregnant woman without complications.